Development of mesoscale oscillatory baffled reactor (MOBR) for bioethanol production - Syamsutajri, Syamsol Bahri (2016)
Oscillatory flow can enhance mass transfer, mixing in flocculation, low shear and controllable mixing conditions. A recent development in oscillatory baffled reactor technology is down-scaling the reactor, so that it can be used for applications such as small-scale continuous production of bioethanol. In the current study, a new design of mesoscale oscillatory baffled reactor (MOBR) with central baffle system was developed and fabricated at “mesoscales” (typically 5 mm diameter). The mixing conditions inside the MOBR were evaluated and the reactor performance was analyzed for bioethanol production. The mixing conditions inside the MOBR were analyzed by evaluating the residense time distribution (RTD) against the dynamic parameters of net flow Reynolds number (Ren) at 4.2, 8.4 and 12.6 corresponding to flow rates of 1.0, 2.0 and 3.0 ml/min respectively, oscillatory Reynolds number (Reo) between 62 to 622 and Strouhal number (Str) between 0.1 to 1.59. The effect of oscillation frequency, oscillation amplitude, net flow, oscillation flow on RTD performance and dependence of the fluid mixing on the velocity ratio were also studied at frequency, amplitude and velocity ratio ranging from 4 to 8 Hz, 1 to 4 mm and 1 to 118 respectively. Next, the reactor performance of the MOBR was compared with conventional stirred tank reactor (STR) to evaluate the bioethanol fermentation performance using Sacchromyces cerevisiae at similar power density of 24.21, 57.38, 112.35 and 193.67 Wm-3 by varying frequency (f), amplitude (xo) and agitation speed. Then the biomass concentration, glucose consumption and bioethanol concentration were analyzed using cell dry weight (CDW), 3,5-dinitrosalicyclic acid (DNS) and high performance liquid chromatograph (HPLC) methods, respectively. It was observed that the MOBR improved the mixing intensity resulted in lower glucose consumption 0.988 gL-1 obtained after 12 hours and the bioethanol concentration 38.98 gL-1 at power density of 193.67 Wm-3. Overall, an improvement of 24.1% yield of bioethanol was generated using MOBR as STR only produced the highest yield of 15.4%.